Mixotrophic culture of bait microalgae for biomass and nutrients accumulation and their synergistic carbon metabolism. (January 2023) - Bo, Yahui; Chu, Ruirui; Sun, Danni; Deng, Xiangyuan; Zhou, Chengxu; Yan, Xiaojun; Ruan, Roger; Cheng, Pengfei
Graphical abstract: Highlights: Six bait microalgae were tested in the mixotrophic culture. The suitable organic carbon for T. pseudonana and Chlorella sp. are different. Optimized organic carbon and nitrogen improve growth and metabolites accumulation. Carbon utilization pathways in mixotroph is related to the microalgae species. Abstract: Microalgae cannot meet the bait demand for aquaculture due to light intensity limitation and other disadvantageous conditions. This research selected 6 mixotrophic microalgae, and the optimal strains and organic carbon were screened. The results showed that Thalassiosira pseudonana and Chlorella sp. are suitable for mixotrophic culture. The maximum cell density of Thalassiosira pseudonana was found to be 1.67 times than that of the photoautotrophic group when glycerol was added. The maximum cell density of Chlorella sp. with acetic acid was 1.69 times than that of the photoautotrophic group. When the concentration of acetic acid was 5.0 g·L -1 and the concentration of KNO3 was 0.2 g·L -1, the maximum biomass of Chlorella sp. could reach 3.54 × 10 7 cells·mL −1 ; the maximum biomass of Thalassiosira pseudonana was 5.53 × 10 6 cells·mL −1 with 10.0 g·L -1 glycerol and 0.2 g·L -1 KNO3 . Metabolomic analysis further revealed that mixotrophic bait microalgae could promote the accumulation of lipids and amino acids.